Prognostic value of end-of-induction PET response after first-line immunochemotherapy for follicular lymphoma (GALLIUM) secondary analysis of a randomised, phase 3 trial - Trotman Judith; Barrington Sally F.; Belada David; Meignan Michel; MacEwan Robert; Owen Carolyn; Ptáčník Václav; Rosta András; Fingerle-Rowson Günter R .; Zhu Jiawen; Sahin Deniz; Hiddemann Wolfgang; et al. (2018)
Initial results from the ongoing GALLIUM trial have shown that patients with follicular lymphoma have a longer progression-free survival after first-line immunochemotherapy with obinutuzumab than with rituximab. The aim of this secondary analysis was to evaluate the prognostic value of PET-CT responses after first-line immunochemotherapy in the GALLIUM study.GALLIUM is an open-label, parallel-group randomised, phase 3 trial, which recruited previously untreated patients with CD20-positive follicular lymphoma (grades 1-3a; disease stage III/IV, or stage II with largest tumour diameter ≥7 cm) who were aged 18 years or older and met the criteria for needing treatment. Eligible patients were randomly assigned in a 1:1 ratio to receive intravenous administration of obinutuzumab (1000 mg on days 1, 8, and 15 of cycle 1, then day 1 of subsequent cycles) or rituximab (375 mg/m2 on day 1 of each cycle), in six 21-day cycles with cyclophosphamide, doxorubicin, vincristine, and prednisone (known as CHOP; oral administration) followed by two 21-day cycles of antibody alone, or eight 21-day cycles cyclophosphamide, vincristine, and prednisone (known as CVP; oral administration), or six 28-day cycles with bendamustine, followed by maintenance antibody every 2 months for up to 2 years. The primary endpoint of the trial, investigator-assessed progression-free survival, has been reported previously. This secondary analysis reports PET and CT-based responses at end-of-induction therapy and explains their relation with progression-free and overall survival outcomes in patients with available scans. As per protocol, during the trial, PET scans (mandatory in the first 170 patients enrolled at sites with available PET facilities, and optional thereafter), acquired at baseline and end of induction (PET population), were assessed prospectively by investigators and an independent review committee (IRC) applying International Harmonisation Project (IHP) 2007 response criteria, and retrospectively by the IRC only applying current Lugano 2014 response criteria. IRC members (but not study investigators) were masked to treatment and clinical outcome when assessing response. The landmark analyses excluded patients who died or progressed (contrast enhanced CT-based assessment of progressive disease, or started next anti-lymphoma treatment) before or at end of induction. GALLIUM is registered at ClinicalTrials.gov, number NCT01332968.1202 patients were enrolled in GALLIUM between July 6, 2011, and Feb 4, 2014, of whom 595 were included in the PET population; 533 (IHP 2007; prospective analysis), and 508 (Lugano 2014; retrospective analysis) were analysed for progression-free survival (landmark analysis). At end of induction, 390 of 595 patients (65·5% [95% CI 61·6-69·4]) achieved PET complete response according to IHP 2007 criteria, and 450 (75·6% [95% CI 72·0-79·0]) obtained PET complete metabolic response according to Lugano 2014 criteria. With a median of 43·3 months of observation (IQR 36·2-51·8), 2·5-year progression-free survival from end of induction was 87·8% (95% CI 83·9-90·8) in PET complete responders and 72·0% (63·1-79·0) in non-complete responders according to IRC-assessed IHP 2007 criteria (hazard ratio [HR] 0·4, 95% CI 0·3-0·6, p<0·0001). According to Lugano 2014 criteria, 2·5-year progression-free survival in complete metabolic responders was 87·4% (95% CI 83·7-90·2) and in non-complete metabolic responders was 54·9% (40·5-67·3; HR 0·2, 95% CI 0·1-0·3, p<0·0001).Our results suggest that PET is a better imaging modality than contrast-enhanced CT for response assessment after first-line immunochemotherapy in patients with follicular lymphoma. PET assessment according to Lugano 2014 response criteria provides a platform for investigation of response-adapted therapeutic approaches. Additional supportive data are welcomed.F Hoffmann-La Roche.
Keywords: Klinikai orvostan